Exploring the patriarchal limits of liberal democracy. Spanish feminist movement’s shift from institutional to protest struggle - Fallada García-Valle, Juan Ramón (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Some expressions identify the constitutional order with the “rules of the game” or “of the convivence”. Taking that as a starting point, some key characteristics of the constitutional orders are pointed out, by comparing them with the rules of the games. Freedom, ludic character and lack of punishment to those who decide not to play are confronted to supposed shared consent of the constitutional norms, sacredness and potential use of unregulated violence against dissidence. From that characterization some critical comments will be made.